Family capital: Examining social capital, family commitment, and acculturation among college-enrolled Mexican-American men and women in the Southwestern United States. Issue 2 (14th March 2016) - Archuleta, Adrian J.; Perry, Armon R.
ABSTRACT: Social capital is integral to an individual's ability to access various resources embedded in social and familial networks that are important in academic access and future success. The types and dynamics of social relationships created by men and women are thought to generate different forms of social capital with factors such as acculturation resulting in differences in intercultural networks and potential resource access. However, the factors that contribute to the development of social capital require further investigation. The current study examines the relationship between acculturation, family role commitment, and various social network characteristics associated with social capital among Mexican-American college-enrolled men ( n  = 119) and women ( n  = 196). Several multiple regressions were conducted. Findings indicate that acculturation and family role commitment relate differently to social-capital-network characteristics among Mexican-American men and women. For women, marital commitment was consistently related to social-capital-network characteristics whereas acculturation factors seemed to be more salient among men. Overall, study variables accounted for a larger portion of the variance for social-capital-network characteristics across analyses for men than women indicating that other factors may be at play in generating social capital for women.